DARI RITUAL MENUJU FESTIVAL: BANJIR DAWET DESA BANJARDOWO, KABUPATEN JOMBANG 1970-2019 - Ananta Dharma Kusuma (Historiography: Journal of Indonesian History and Education, 2021)
Festival is a form of human joy that is expressed in the form of an exhibition. The festivals that are held can be of micro or macro types depending on the context of the celebration itself. Various examples of micro-scale festivals have been held, including in the village of Banjardowo Jombang, East Java. The festival held in the village is culinary delicacy with the name dawet flood. This study uses historical methods using sources in the form of articles, books, bold news, documentary videos and interviews. This study shows that the dawet flood underwent a transformation from what was originally a ritual shift to a festival in the form of village alms. The name of this festival has even come out in the ears of the people outside the village and a lot of outsiders have flocked to Banjardowo Village just to take part in the festival.Festival merupakan salah satu bentuk kegembiraan manusia yang dituangkan dalam bentuk perayaan. Festival yang diselenggarakan bisa berjenis mikro maupun makro tergantung konteks perayaan itu sendiri. Berbagai macam contoh festival skala mikro banyak terselenggara tak terkecuali di Di Desa Banjardowo Jombang, Jawa Timur. Festival yang diselenggarakan di desa tersebut bercorakkan kuliner dengan nama banjir dawet. Penelitian ini menggunakan metode sejarah dengan menggunakan sumber-sumber berupa artikel, buku, berita daring, video dokumenter dan juga hasil wawancara. Studi ini menunjukkan bahwa banjir dawet mengalami sebuah tranformasi dari yang pada awalnya bersifat ritual bergeser menjadi sebuah festival berbentuk sedekah desa. Nama festival ini bahkan sampai keluar di telinga masyarakat luar desa dan banyak sekali masyarakat luar yang berbondong-bondong datang ke Desa Banjardowo hanya untuk mengikuti festival.